Strengthening Community Religious Understanding Through Community-Based Religious Study Activities - Arditya Prayogi; M. Adin Setyawan; Riki Nasrullah; Imam Prayogo Pujiono; Moh. Syaifuddin (Jurnal Pengabdian IPTEK, 2026)
Strengthening the community's religious understanding is a crucial need amidst the social dynamics of the digital era, including low self-control and emotional management abilities that impact the quality of individual relationships with others. This community service activity aims to strengthen the understanding and practice of religious values ​​through a public religious study welcoming Ramadan with the theme "When Hunger Teaches Patience: Controlling Reactions, Gaining Self-Control." The activity was carried out by involving the surrounding community and the participants of the study as the main target. The method used was service learning through three stages: planning, implementation, and evaluation, as well as a mau'izhah hasanah approach in delivering the material that emphasized strengthening patience, controlling reactions, and spiritual readiness to welcome Ramadan. The results of the activity showed an increase in the participants' religious understanding, particularly in the aspects of morality and self-control as a practice of faith values ​​in daily life. Participants not only gained a normative understanding of patience and fasting, but were also able to rationalize and formulate applicable steps to manage emotions and build more consistent worship habits. This community-based public religious study activity has proven effective as a model of community service to strengthen religious awareness and spiritual readiness in the community ahead of Ramadan.